2019
DOI: 10.12973/ijem.5.1.275
|View full text |Cite
|
Sign up to set email alerts
|

A Study on Art Interests and Critical Thinking Dispositions of Students in Fine Arts Department of the Faculty of Education

Abstract: In this study, it was aimed to investigate the relationship between the art interests and critical thinking dispositions of the students who study fine arts education in the faculty of education. The sample of the research consisted of 236 fine arts education students including 123 from the department of painting teaching and 113 from the department of music education. In the research, relational survey method was used. It was found in the research that the art interests of the students were at the level that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 10 publications
(10 reference statements)
1
5
0
1
Order By: Relevance
“…The findings supported previous studies (Walsh & Hardy, 1999;Giancarlo & Facione, 2001;Lampert, 2007;Liu & Zhao, 2010;Wen, 2012;Taskesen, 2019), which claimed that differences were found in CT dispositions among college students of different majors. However, the most striking difference was the non-significant variance in the majority of subscales between the two discipline groups in this study.…”
Section: Major and Ct Dispositionssupporting
confidence: 91%
See 2 more Smart Citations
“…The findings supported previous studies (Walsh & Hardy, 1999;Giancarlo & Facione, 2001;Lampert, 2007;Liu & Zhao, 2010;Wen, 2012;Taskesen, 2019), which claimed that differences were found in CT dispositions among college students of different majors. However, the most striking difference was the non-significant variance in the majority of subscales between the two discipline groups in this study.…”
Section: Major and Ct Dispositionssupporting
confidence: 91%
“…Secondly, differences in subscale mean scores of CT dispositions were related to students' majors. There was a positive moderate relationship between art interest and analyticity, inquisitiveness; a significantly low positive relationship between art interest and self-confidence, systematicity, truth-seeking, cognitive maturity (Taskesen, 2019), but fine arts undergraduates scored significantly higher than non-arts undergraduates on truth-seeking, critical thinking maturity and open-mindedness (Lampert, 2007). Science students got significantly higher scores in truth-seeking than social science students, while the latter got higher scores in analyticity (Liu & Zhao, 2010).…”
Section: Major and Ct Dispositionsmentioning
confidence: 88%
See 1 more Smart Citation
“…Also, Sirichat's study (2007) defined that Thai students with distinctive academic achievement tended to demonstrate similar critical thinking characteristics. Taskesen (2019) studied on students in the Faculty of Education in Turkey, it was found that there was no remarkable difference in critical thinking disposition among 1st to 4th year undergraduate Turkish students, and gender might not be related to critical thinking disposition. Abiogu et al, (2020) investigated critical thinking disposition of undergraduate nursing students, it was found that there was no significant difference among undergraduate nursing students.…”
Section: Critical Thinking Dispositions Among Undergraduate Studentsmentioning
confidence: 97%
“…Disposisi menuju berpikir kritis merupakan kecenderungan untuk mempengaruhi tindakan dalam kondisi tertentu [13][14] [15]. Kecenderungan dimiliki setiap individu untuk berpikir sesuai kondisi tertentu [16].…”
Section: Metodeunclassified